Regulation by adrenal corticosteroids of sodium and potassium transport in loop of Henle and distal tubule of rat kidney. - Stanton, B A (1986)
Studies were conducted to examine the effects of adrenalectomy (ADX) and selective, physiological adrenal corticosteroid replacement on sodium and potassium transport by the superficial loop of Henle and distal tubule of rat kidney in vivo. In the loop of Henle, ADX inhibited sodium reabsorption by 33%. Whereas dexamethasone had no effect on reabsorption, aldosterone increased sodium transport to control levels. Thus, physiological levels of mineralocorticoids, but not glucocorticoids, control a fraction of sodium reabsorption in the loop of Henle. ADX also inhibited potassium reabsorption in the loop of Henle. Both dexamethasone and aldosterone reversed the inhibition, although only aldosterone increased reabsorption to control levels. In the distal tubule, ADX reduced sodium reabsorption by 44%. Both aldosterone and dexamethasone stimulated reabsorption: however, only aldosterone increased transport to control. Potassium secretion by the distal tubule was also reduced 34% by ADX. Aldosterone, but not dexamethasone, stimulated secretion. Thus, physiological levels of aldosterone regulate a fraction of sodium reabsorption and potassium secretion in the distal tubule.